The effect of pacing strategy on physiological, kinetic and performance variables during simulated rowing ergometer - Dimakopoulou, E.; Zacharogiannis, E.; Chairopoulou, C.; Kaloupsis, S.; Platanou, T. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study compared the effects of self-selected (SSP), negative (NPS), and even pacing strategy (EPS) on performance time, and kinetic and physiological variables in overall 2-km rowing and in first and second 1 km. METHODS: Fifteen male rowers (15.37±1.34 years) realized four tests: an incremental test on a rowing ergometer to determine their VO2peak and three experimental 2-km rowing race, where first 1 km was manipulated. From SSP a negative pacing strategy, 4% slower than the mean velocity of SSP, and an even pacing strategy (EPS) with mean velocity of SSP, were developed. RESULTS: High stroke rate and better performance time were observed in SSP. Fstr and Fpeak decreased, whereas performance time increased, in SSP and EPS from first to second 1 km. However, performance time, stroke rate and Pst in NPS presented better values (P=0.001) with the exception of decreased stroke length (P=0.03). There was an increase in physiological responses in all pacing strategies from first to second 1 km (P=0.001). Performance time, stroke rate and Fstr were better in SSP and EPS compared to NPS in first 1 km (P=0.001). VE, VE/VO2, VCO2 were better in SSP and EPS compared to NPS (P=0.001) in both first and second 1 km. Stroke length was smaller in SSP compared to NPS and EPS in second 1 km (P=0.001). CONCLUSIONS: SSP (parabolic-shaped profile) allowed rowers to cover the 2-km distance at higher stroke rate and in shorter performance time compared to negative and even pacing strategies presenting same physiological responses.